Colonic Salvage With Antiperistaltic Cecorectal Anastomosis. Issue 2 (February 2015) - Jones, Douglas W.; Dimitrova, Maya; Nandakumar, Govind
<x xml:space="preserve">Abstract</x> BACKGROUND: Following colon resection, the construction of a well-perfused, tension-free isoperistaltic anastomosis can be made difficult by multiple factors including prior abdominal surgery or compromised vascular supply. Here, we describe the technique of antiperistaltic cecorectal anastomosis as a method for preserving viable colon without compromising functional outcome. TECHNIQUE: Following extensive colorectal resection, different techniques for isoperistaltic reconstruction using the cecum and ascending colon have been described, including the Deloyers procedure and limited isoperistaltic cecorectal anastomosis. However, these isoperistaltic reconstructions often require ligation of the middle colic and right colic arteries and/or sacrifice of viable distal colon to aid reconstruction. In complex situations that require preservation of normal vascular anatomy, an antiperistaltic cecorectal anastomosis can be constructed that maintains the orientation of the vascular pedicle. In addition to the preservation of the colonic arterial supply, a distinguishing feature of this technique is the substantial portion of antiperistaltic colon that is preserved and interposed to reestablish continuity. RESULTS: In a case where it was used, construction of an antiperistaltic cecorectal anastomosis was technically successful and led to a good functional outcome. CONCLUSION: Antiperistaltic cecorectal anastomosis should be considered as an option in colonic reconstruction for patients with extensive prior abdominal surgery or when complex anatomic issues require preservation of native vascular anatomy. In these situations, this technique offers several advantages over isoperistaltic reconstruction and may be the only option for reconstruction that uses the remaining cecum and colon.